1995
DOI: 10.1091/mbc.6.12.1769
|View full text |Cite
|
Sign up to set email alerts
|

BET3 encodes a novel hydrophilic protein that acts in conjunction with yeast SNAREs.

Abstract: Here we report the identification of BET3, a new member of a group of interacting genes whose products have been implicated in the targeting and fusion of endoplasmic reticulum (ER) to Golgi transport vesicles with their acceptor compartment. A temperature-sensitive mutant in bet3-1 was isolated in a synthetic lethal screen designed to identify new genes whose products may interact with BET1, a type II integral membrane protein that is required for ER to Golgi transport. At 37 degrees C, bet3-1 fails to transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 36 publications
4
77
0
Order By: Relevance
“…The complex process may require an intermolecular regulatory role in addition to the intramolecular regulation of SNARE domains in the formation of the core complexes. Bet3p, a component of TRAPP, was shown to interact genetically with yeast SNAREs and is required for vesicle targeting and fusion (37). SEDL, as a component of human TRAPP, may be responsible for the interaction with a SNARE protein.…”
Section: Resultsmentioning
confidence: 99%
“…The complex process may require an intermolecular regulatory role in addition to the intramolecular regulation of SNARE domains in the formation of the core complexes. Bet3p, a component of TRAPP, was shown to interact genetically with yeast SNAREs and is required for vesicle targeting and fusion (37). SEDL, as a component of human TRAPP, may be responsible for the interaction with a SNARE protein.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the extended structure of Uso1, which is predicted to span a distance of .180 nm (Yamakawa et al 1996), the multisubunit TRAPPI complex is required for COPII-dependent transport to Golgi acceptor membranes (Rossi et al 1995;Sacher et al 1998). In vitro assays revealed that TRAPPI can also function to physically link COPII vesicles to Golgi membranes (Sacher et al 2001).…”
Section: Vesicle Tetheringmentioning
confidence: 99%
“…The Bet3 protein is an essential component of the trafficking protein particle (TRAPP) complex (Menon et al, 2006), which, together with SNAREs and Rab-GTPases (Kim et al, 2005;Loh et al, 2005;Rossi et al, 1995;Sacher et al, 2008), is involved in vesicular transport in eukaryotic cells. We report here that NS5A from BVDV interacts physically with NIBP and inhibits NF-kB activation, which may play a role in BVDV pathogenesis.…”
Section: Introductionmentioning
confidence: 99%